Supporting families experiencing homelessness : current practices and future directions - Haskett, Mary E.; Perlman, Staci; Cowan, Beryl Ann (New York, NY : Springer, 2014)
With more American families being increasingly forced into homelessness, this book aims to raise the standard and scope of services provided to families without homes through practices that are both strengths-based and culturally competent. All major aspects of this important topic are analyzed, with recommendations for what is needed to improve current programs or establish new ones. Chapters set out the particular needs of parents, children, and teens as well as homeless subpopulations, such as youth who age out of foster care. This book presents a real-world framework for services that are client-centered, are integrated across provider systems, and follow families in their transition to stable housing. Included in this volume: The ecology of family homelessness. Developmental and mental health outcomes of sheltered infants, children, and adolescents. Parenting in the face of homelessness. Trauma-informed practices in shelters and other programs serving homeless families. Cultural competence and individualized care in service provision. Evidence-based and promising approaches to service provision and intervention. A groundbreaking volume, this book is a must-read for students preparing for careers in human services, all frontline providers working with those at-risk for housing instability or currently living without homes, and researchers and policy-makers working to enhance outcomes for families experiencing homelessness.
I. Needs of Children and Families Experiencing Homelessness -- The Why and the Who of Family Homelessness -- The Developmental Trajectories of Infants and Young Children Experiencing Homelessness -- Trauma Exposures and Mental Health Outcomes among Sheltered Children and Youth ages 6-18 -- Parenting in the Face of Homelessness -- Needs of Special Populations of Families without Homes -- II. Frameworks for Service Delivery and Intervention for Families -- Collaborations Across and Within Systems that Provide Services to Families without Homes -- Trauma-Informed Care for Families Experiencing Homelessness -- Cultural Competence and Individualized Care in Service Provision -- III. Evidence Based and Promising Approaches to Service Provision and Intervention -- Research on Programs Designed to Support Positive Parenting -- Programs for Homeless Children and Youth: A Critical Review of Evidence -- Primary Stakeholders' Perspectives on Services for Families without Homes.
Includes bibliographical references and index.
Keywords: Homeless families